FloraVeg.EU — An online database of European vegetation, habitats and flora - Chytrý, Milan; Řezníčková, Marcela; Novotný, Petr; Holubová, Dana; Preislerová, Zdenka; Attorre, Fabio; Biurrun, Idoia; Blažek, Petr; Bonari, Gianmaria; Borovyk, Dariia; Čeplová, Natálie; Danihelka, Jiří; et al. (Applied vegetation science, 2024)
This article describes FloraVeg.EU, a new online database with open‐access information on European vegetation units (phytosociological syntaxa), vegetated habitats, and plant taxa. It consists of three modules. (1) The Vegetation module includes 149 phytosociological classes, 378 orders and 1305 alliances of an updated version of the EuroVegChecklist modified based on the decisions of the European Vegetation Classification Committee. Vegetation units dominated by vascular plants are characterized by country‐based distribution maps and data on the dominant life forms, phenology, soil properties, relationships to vegetation regions, elevational vegetation belts and azonal habitats, successional status, and degree of naturalness. A list of diagnostic taxa is also provided for each class. (2) The Habitats module includes vascular‐plant‐dominated terrestrial, freshwater, and marine habitat types from the first to the third or fourth highest hierarchical levels of the EUNIS classification. Of these, 249 vegetated habitats are characterized by a brief description, a point‐based distribution map, diagnostic, constant, and dominant taxa, and a list of the corresponding alliances. (3) The Species module provides information on 37 characteristics of European vascular plant species and some infrageneric or infraspecific taxa, including functional traits (habitus and growth type, leaf, flower, fruit and seed traits, and trophic mode), taxon origin (native vs alien), and ecological information (environmental relationships, Ellenberg‐type indicator values, disturbance indicator values, and relationships to vegetation units and habitat types). Values for at least three variables are available for 36,404 species. Individual taxa, vegetation units, and habitats in these three modules are illustrated by more than 34,000 photographs. The Download section of FloraVeg.EU provides open‐access data sets in a spreadsheet format that can be used for analyses. FloraVeg.EU is a new resource with easily accessible data that can be used for research in vegetation science, ecology, and biogeography, as well as for education and conservation applications. FloraVeg.EU is a new online database of European vegetation, habitats and flora. The Vegetation module contains an updated standard European vegetation classification (EuroVegChecklist). The Habitats module includes vascular‐plant‐dominated habitat types of the EUNIS habitat classification. The Species module provides information on functional traits, origin, and ecology of European vascular plant taxa.